MANAJEMEN KOMPENSASI KARYAWAN DI PT BNI 46 SUDIRMAN JAKARTA - Zainuddin, Zulkifli; Nugroho, Agung (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
The purpose of this study is to examine the difference of employee compensation and to identifying the main type of compensation at PT BNI 46 Sudirman Jakarta. The study design was quantitative research by using independent samples t-test. Data were collected from 60 employees using questionnaire with random sampling method. This study finds that there is significant differences response between two-group samples. The main types of compensation are financial and non-financial compensation. Financial compensation, namely: wages and compensation based on the achievement of the job target. While the type of non-financial compensation is a major career development or job promotions. Keywords: financial compensation